2011
DOI: 10.3171/2010.4.jns1079
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and stereotactic aspiration treatment of cerebral sparganosis: summary of 11 cases

Abstract: The authors concluded that an effective preoperative diagnosis of cerebral sparganosis can be made by detailed inquiry into the possible infection history and disease symptoms as well as careful scrutiny of characteristic radiological features and immunological testing results. In stereotactic operations performed to remove the larva, priority should be given to image-guided stereotactic aspiration given that it causes the smallest wounds. In cases in which stereotactic aspiration fails, stereotactic microsurg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
39
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 25 publications
0
39
0
3
Order By: Relevance
“…The treatment of choice for cerebral sparganosis is surgical removal because treatment with antihelmintics, including praziquantel, has been described as not effective [1][2][3]. In our patient the clinical improvement, and the normalisation of brain imaging and of anti-sparganum antibody levels suggest that the parasite was eradicated by high dose praziquantel therapy.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…The treatment of choice for cerebral sparganosis is surgical removal because treatment with antihelmintics, including praziquantel, has been described as not effective [1][2][3]. In our patient the clinical improvement, and the normalisation of brain imaging and of anti-sparganum antibody levels suggest that the parasite was eradicated by high dose praziquantel therapy.…”
mentioning
confidence: 66%
“…The patient was suspected to have neurocysticercosis and was treated with albendazole Surgical removal of the parasite is the treatment of choice as standard antihelmintic therapy is considered ineffective in sparganosis [1][2][3]. The repeated MRI indicated that the lesion had been wandering again (D and J).…”
mentioning
confidence: 99%
“…7 The postulated route of sparganum infestation to the brain is that first it passes through the alimentary canal to the abdominal cavity; then it penetrates the diaphragm and mediastinum upwards to reach the neck, where it further migrates up through the foramen magnum or jugular foramen; and finally, it reaches the brain. 8 A definite diagnosis of cerebral sparganosis is challenging due to its nonspecific clinical manifestation. Previously, it was often misdiagnosed as a neoplasm, 9 infarct, 10 tuberculoma, 11 or other diseases.…”
mentioning
confidence: 99%
“…With the availability of high-resolution CT and MR imaging, the ELISA test for parasitic antibodies, and stereotactic biopsy, more cases of sparganosis are being diagnosed currently. 8,12 Characteristic imaging features like the "tunnel"…”
mentioning
confidence: 99%
“…11 Su incidencia en nuestro medio está relativizada debido a la ausencia de manifestaciones clínicas características y, desde el punto de vista histológico, por la presencia de una respuesta granulomatosa, inespecífica si no se logra visualizar el parásito. En la gran mayoría de los casos el diagnóstico de estas formas cerebrales es posquirúrgico e histopatológico.…”
Section: Discussionunclassified